Community Perception in Preventing Cases of COVID-19 in Bogor City in 2020 - Letelay, Alfons Maryono; Manalu, Helper Sahat Parulian; Senewe, Felly Philipus; Tobing, Kristina L; Shinta, Shinta; Wahidin, Mugi (Global Medical & Health Communication (GMHC), 2023)
The COVID-19 outbreak of a coronavirus that causes illness shocked the world. Health precautions must be implemented to limit the number of COVID-19 cases or prevent transmission. This study aims to ascertain the public's perception of the COVID-19 case in the community. This report is one of the findings of a survey of the association between comorbidities and preventative behavior in COVID-19 cases, specifically public perceptions of COVID-19 cases in Bogor city. This study took place from March through the end of September 2020. Data were obtained through in-depth interviews utilizing a guideline developed based on the parameters of a qualitative study. The prior recommendations were validated, and the data was represented using transcripts and a data matrix to aid in the descriptive data analysis. According to a study on public views of COVID-19, individuals realize the risks they face if they do not adhere to the government's health protocols. According to quantitative data, the proper use of masks when outside the home is only 18.0%, the correct use of hand sanitizers is 26.2%, the correct use of soap is 80.3%, the proper use of hand sanitizers is 90.2%, and the correct coughing and sneezing behavior is 60.7%. In general, research data findings have not been encouraging for COVID-19 prevention; therefore, you will be prone to COVID-19 infection if you disregard health regulations, particularly by correctly wearing masks. As a result, in general, the findings of public perception have not been able to diminish the number of COVID-19 instances.